Oscillator strength and carrier dynamics in type I and inverted type I spherical core/ shell nanostructures under external laser field. (November 2019) - Anitha, B.; Nithiananthi, P.
Abstract: For the first time, the effect of laser on the donor impurity states in spherical nano core/shell systems is examined theoretically by variation technique. In this work, a step like laser dressed confinement potential is employed to evolve the donor dynamics in two different spherical core/shell quantum structures namely (a) Type I GaAs/Al0.3 Ga0.7 As core shell nanostructure (CSN) and (b) Inverted Type I Al0.3 Ga0.7 As/GaAs CSN. Donor binding energy (BE) is calculated for various laser dressing parameter ( α 0 ) for various impurity locations (Ri ) by varying the dimensions of the systems. Effect of laser on sub-level energy (E0 ), oscillator strength (P10 ), transition energy (E10 ) and the magnitude of dipole matrix element ( | M 10 | ) of the systems are also determined. The diverse behavior of type I and inverted type I CSNs are analyzed. It is witnessed that in type I the carrier is highly confined whereas inverted type I favors tunneling. This study will help in understanding the influence of laser field on donor impurity in CSNs and its application towards optical devices. Highlights: Screening effect of laser alters the Subband Energy resulting in lowering of Binding Energy. Threshold intensity of CO2 laser for the onset of carrier ionization in Core/Shell Nanostructure is 4.8 μW/nm 2 . In type I, the contribution of dipole matrix element is larger than the transition energy. In inverted type I Core/Shell nanostructure oscillator strength decreases with laser parameter. Localization of carrier in type I Core/Shell nanostructure is always higher than inverted type I.